Role of Systematic Lymphadenectomy to Tailor Adjuvant Therapy in Early Endometrial Cancer. Issue 1 (January 2018) - Nama, Vivek; Patel, Amit; Kirk, Lisa; Murdoch, John; Bailey, Joanne
Abstract : Objective: The long-standing protocol at our center for apparent stage I and II endometrial cancers comprises hysterectomy and bilateral salpingo-oophorectomy without lymphadenectomy. Adjuvant treatment is based in line with Postoperative Radiation Therapy in Endometrial Carcinoma 1 protocol. Our aim was to quantify the number of patients who would avoid external beam radiation therapy (EBRT) in our institution if we adopted a protocol of lymphadenectomy to tailor adjuvant EBRT and its impact on cost and quality of life. Design: Retrospective case-cohort study. Setting: Gynecological oncology center. Methods: All endometrial cancers treated from 2007 to 2012 were included. The European Organization for Research and Treatment of Cancer (EORTC) quality of life (QLQ-30) and endometrial cancer specific (EN-24) questionnaires were used to measure the quality of life. The NHS tariff for EBRT, VBT and lymphadenectomy were obtained from our Trust's contract with the local commissioning groups. Main Outcome Measures: Quality of life and cost. Results: Systematic pelvic lymphadenectomy in early endometrial cancers of all grades would avoid EBRT in 23.3% of patients, and if performed for grade 2 and 3 cancers, 39.5% of patients would avoid EBRT. The global health scores were significantly lower, and pain scores were considerably higher in patients who received EBRT. Performing systematic lymphadenectomy and tailored adjuvant therapy in grade 2 and 3 endometrial cancers would save £134, 691 and for all grades save £37, 161 for every 100 patients treated with early endometrial cancer. Conclusion: Systematic lymphadenectomy with tailored adjuvant therapy may offer better QoL with reduced cost to NHS without a reduction in overall survival.